Food and nutrition security implications of crop diversification in Malawi’s farm households - Mazunda, John; Kankwamba, Henry; Pauw, Karl (International Food Policy Research Institute, 2015)
Although dramatic increases in maize yields since the implementation of the Farm Income Subsidy Program (FISP)—the major national program that subsidizes fertilizer and improved seed primarily for maize cultivation—have likely enhanced household maize self-sufficiency (Chibwana et al. 2012), Malawian diets remain poorly diversified. Indeed, the contribution of foods other than maize to national per capita dietary energy supply appears to have actually decreased slightly in recent years. Poorly diversified diets characterized by an overreliance on starchy staples are a red flag for malnutrition. Conversely, diets which include a variety of foods are considered important for positive health. Diets which include nutrient-rich legumes and animal-source foods as well as vitamin-rich fruits and vegetables are associated with micronutrient adequacy and reductions in chronic undernutrition (Arimond and Ruel 2004; Thompson and Amoroso 2011).